Hiding in the Spotlight: Commodifying Nature and Geographies of Dissociation in the Fur-Fashion Complex. (1st January 2021) - Müller, Felix C.; Kleibert, Jana M.; Ibert, Oliver
Abstract: Multiple challenges plague actors that commodify nature and create markets around products made from natural organisms. Primary among these is the reputational risk that results from negative impressions and moral contestations such as animal abuse, bad labor conditions, or pollution. In this contribution, we draw on cultural economic geography, and in particular the concept of dissociation, to demonstrate how supply side actors deal with such threats to their reputation. Geographies of dissociation provide a spatial perspective on the social construction of economic value, with a particular focus on the purposeful obfuscation of practices and the disconnection of discourses. We use the fur-fashion complex as a single case study, representing an extreme but instructive example, to study the agencies and effects of dissociative practices empirically. During our in-depth qualitative research on both the production and consumption of fur fashion, we focus on proactive and reactive dissociative strategies of the most powerful commercial actors in the field: fur-breeder associations and retail brands/brand owners.